A digital game-based learning framework for enhancing primary school students’ critical thinking skills / Mahmood Haitham Hussein - Mahmood Haitham , Hussein (2021)

(untitled)
Critical thinking is an essential skill that helps people to achieve success in a 21st-century global market that favours individuals capable of thinking critically. However, more traditional teaching methods have fallen short in terms of enhancing students’ critical thinking skills. Thus, researchers are exploiting recent technological developments to incorporate technology in education. Among various other technology-supported teaching methods, digital game-based learning (DGBL) has been identified as an effective approach to promoting students’ interest in learning and improving their critical thinking. Despite this interest, however, research shows that there is a paucity of DGBL applications based on specific frameworks, especially in the area of critical thinking. This research addresses this issue by proposing a framework comprising 6 components – inquiry, communication, mystery, decision making, challenge, and rewards (ICMDCR) – that aims to improve primary school students’ critical thinking. It was hypothesised that the ICMDCR framework would significantly improve students’ critical thinking and science subject scores. The researcher conducted a quasi-experimental study with an experimental group (N = 62) and a control group (N = 62) to test these hypotheses and assess the effectiveness of the framework. Results from repeated-measures analysis of variance (ANOVA) and post-hoc Bonferroni tests revealed that only students in the experimental group who played Ecoship Endeavour significantly improved their critical thinking (pre-test = 12.45, post-test = 15.10) and their science subject scores (pre-test = 56.66, post-test = 77.50). In addition, results showed that students in the control group who were taught via the traditional method experienced a considerable decrease in their critical thinking scores (pre-test = 11.98, post-test = 11.15), while their science scores did not significantly improve (pre-test = 55.32, post-test = 57.68). This framework can assist researchers and game developers in designing DGBL applications that refine students’ critical thinking capabilities. Moreover, students can use this game to enhance their critical thinking and participate in an engaging learning environment.